PENGARUH JOB INSECURITY, BUDAYA ORGANISASI, DAN LINGKUNGAN KERJA TERHADAP KOMITMEN ORGANISASIONAL KARYAWAN PADA PT. ABC - ALFIANDRY, ARIEF; SITYA MULDOVA, LIDYA (E-Jurnal Manajemen Trisakti School of Management (TSM), 2021)
The purpose of this study was to determine the effect of job insecurity, organizational culture, and work environment on employee organizational commitment at PT. Nusa Indah Jaya Utama Bekasi. The population in this study is permanent employees at PT. Nusa Indah Jaya Utama Bekasi. The sampling technique used a census technique or total sampling which collected 55 employees. Data was obtained through a questionnaire with a Likert scale. Data were analyzed using multiple linear regression assisted by SPSS version 25. The results of hypothesis testing for this study indicate that the variable job insecurity has an influence on organizational commitment in a negative direction. Organizational culture and work environment variables have a positive influence On organizational commitment